Changes in kinematics and arm-leg coordination during a 100-m breaststroke swim - Oxford, S. W.; James, R. S.; Price, M. J.; Payton, C. J.; Duncan, M. J. (Journal of Sports Sciences, 2017)
The purpose of this study was to compare arm-leg coordination and kinematics during 100 m breaststroke in 26 (8 female; 18 male) specialist breaststroke swimmers. Laps were recorded using three 50-Hz underwater cameras. Heart rate and blood lactate were measured pre- and post-swim. Arm-leg coordination was defined using coordination phases describing continuity between recovery and propulsive phases of upper and lower limbs: coordination phase 1 (time between end of leg kick and start of the arm pull phases); and coordination phase 2 (time between end of arm pull and start of leg kick phases). Duration of stroke phases, coordination phases, swim velocity, stroke length (SL), stroke rate (SR) and stroke index (SI) were analysed during the last three strokes of each lap that were unaffected by turning or finishing. Significant changes in velocity, SI and SL (P < 0.05) were found between laps. Both sexes showed significant increase (P < 0.05) in heart rate and blood lactate pre- to post-swim. Males had significantly (P < 0.01) faster swim velocities resulting from longer SLs (P = 0.016) with no difference in SR (P = 0.064). Sex differences in kinematic parameters can be explained by anthropometric differences providing males with increased propelling efficiency.